Dengue Virus Detection Using Rt-Pcr Method In Ternate City, North Maluku, Indonesia - Amalan Tomia; Rosmila Tuharea (CV. Inara, 2022)
The Dengue disease is caused by a virus from the family Flaviviridae and there are four distinct, but closely related, virus serotypes that cause dengue (DENV-1, DENV-2, DENV-3 and DENV-4). Dengue virus detection is very important to determine the virus serotype that develops in an area. There are several methods to detect dengue virus based on different targets, namely nucleic acids, viral antigens, and antibodies. This study aims to determine the type of dengue virus serotype in four working areas of the Public Health Center in Ternate City. The sample in this study was the eggs of Aedes sp mosquitoes caught in the homes of DHF sufferers and the houses around them. Collection of mosquito eggs Ae. Aegypti was carried out in four Puskesmas working areas in Ternate City. Ovitrap installation was carried out in 200 houses, with a total of 400 ovitraps. Rearing eggs and dengue virus detection were carried out at the Microbiology Laboratory, LITBAGKES Banjarnegara. The method used in this research is the RT-PCR test. The data analysis of the research results was carried out descriptively. Based on the identification results, the mosquito used in this study was the Aede aegypti mosquito. The results of electrophoresis produced viral RNA with a base length of 100 bp, while the target RNA that had been determined were Den1 = 342 bp, Den2 = 251 bp, Den3 = 538 bp. Den4 = 752 bp. The results of the RT-PCR examination showed that the Ae. aegypti in the four working areas of the Puskesmas did not contain the dengue virus (virus negative).